Application of lesson study to improve the quality of mathematics learning in the era of society 5.0 - Muhakimah, Ihtiyatul; Suparni, Suparni; Azka, Raekha; Hendriantiningtyas, Besti (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2025)
Humans and technology in the 5.0 era of society are inseparable. This is very influential in mathematics learning. Mathematics learning in the current era emphasizes the use of technology as a tool to improve the quality of teaching and learning activities. Therefore, the purpose of this research is to see the application of lesson study to improve the quality of mathematics learning in the era of society 5.0. This type of research is qualitative, with a descriptive method to describe the result of the implementation of the lesson study. The lesson study application consisted of 2 cycles. Each cycle consists of 3 stages, namely plan, do, and see. In the planning stage, the model teacher planned the learning by preparing the teaching module. At the do stage, the model teacher implements learning in accordance with the teaching module that has been prepared. Then, at the seed stage, the model teacher reflects together with the observers. The results of this study showed that in each cycle of the lesson study application, there was an improvement in the quality of learning, such as the reduction of students sleeping, the use of handphones only for learning purposes, and there were 98% of students who were active during teaching and learning activities.